Strategies to Improve Career Planning for Middle School Students - intan fauzana; Afdal Afdal; A Muri Yusuf (SCHOULID: Indonesian Journal of School Counseling, 2021)
This article discusses strategies to improve career planning for middle high school students. Currently, some of the IX middle high school students are having problems in planning their careers. There are still students who don't know where they will go after graduation. There are students who after graduation choose schools at random, based on the choice of their parents or with friends. Here it can be seen that there is no contribution from the student's interests, talents, and desires. Therefore, it is very necessary to have career planning as a process of choosing a career direction, taking into account the opportunities, constraints, and options to achieve the desired career goals according to the potential of students such as talents, interests, intelligence with consultations between counseling teachers, students, and parents or in the form of an instrument. So, it is hoped that counseling teachers at schools have strategies in improving, developing, and directing junior high school students in career planning, and there is nothing wrong in choosing a career for their future.